Nonparametric statistical inference - Gibbons Jean Dickinson; Chakraborti Subhabrata (Boca Raton CRC Press, 2011)
The book presents new material on the quantiles, the calculation of exact and simulated power, multiple comparisons, additional goodness-of-fit tests, methods of analysis of count data, and modern computer applications using MINITAB, SAS, and STATXACT Th
Keywords: Nonparametric inference; Statistical inference